Responsibilities and educational preparation of community nutrition workers engaged in the Philippine nutrition program - Pangan, Maria Raquel L.
The responsibilities and educational preparation of workers engaged in the Philippine Nutrition Program was of 1980 were studied. A questionnaire was used to obtain data from the 1,137 employed in 7 government and private agencies. Most of the nutrition workers were not professional nutritionists. In fact, they represented different fields of study. Majority of the respondents had responsibilities in problem identification, community organization, planning, implementation, evaluation, coordination, documentation and reporting, and supervision but not in research and budgeting/ accounting of funds. The agencies did not differ significantly in terms of proportion of respondents involved in Implementation, Evaluation, Coordination, and Research. They differed in the amount of time spent in all areas of responsibility except Research. The number of respondents engaged in Operation Timbang, Food Production, Income-Generation, Nutrition Rehabilitation, Family Planning, and Training varied significantly across agencies. However, no agency differences were noted in Nutrition Information and Education, Supplementary Feeding and Health Protection. Agencies differed significantly in the amount of time spent in the different nutrition projects except Training. Nutrition Information and Education was considered the most important project, followed by Food Production and Operation Timbang. Of the 60 significant tasks of the workers, 40 were considered easy to do while 20 were adjudged difficult. The areas of responsibility with the most number of difficult tasks were Planning, Coordination, Evaluation and Supervision, Community Organization, and Documentation and Reporting while the area of Implementation was the easiest to perform. Very few had college courses in Community Organization, Community Development and Program Mechanics (Program Planning, Management and Supervision and Evaluation). Respondents expressed a need for additional training in Basic and Applied Nutrition and Program Management. Community nutrition workers indicated that 15 of the 60 tasks were provided adequate educational preparation in college while the rest received less-than-adequate college preparation ratings. These 15 taskes, which were also easy to perform, were distributed in the two areas of Problem Identification and Implementation. There was a significant positive correlation between ease of performing tasks and adequacy of educational preparation for these tasks.